2017
DOI: 10.1186/s13104-017-2577-x
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolative microRNA precursor based SSR mining from tea EST database in respect to agronomic traits

Abstract: Tea (Camellia sinensis, (L.) Kuntze) is considered as most popular drink across the world and it is widely consumed beverage for its several health-benefit characteristics. These positive traits primarily rely on its regulatory networks of different metabolic pathways. Development of microsatellite markers from the conserved genomic regions are being worthwhile for reviewing the genetic diversity of closely related species or self-pollinated species. Although several SSR markers have been reported, in tea, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…In M. truncatula, a total of 169 primer pairs were successfully designed from 130 miRNA genes (Min et al, ); (b) in lotus ( Nelumbo nucifera ), 1,000 bp sequences (500 bp flanking 5′ and 3′ ends) each in 106 pre‐miRNAs were screened for the presence of miR‐SSRs using MISA; 45 miR‐SSRs were identified in 36 genotypes (Wang, Gui, Pan, Hu, & Ding, ). (c) In tea ( Camellia sinensis ), using an online program WebSat, 18 SSRs were identified in 13 of 33 predicted miRNAs that were located in ESTs; primer pairs flanking each SSR were designed with the help of BatchPrimer3 server (Hazra, Dasgupta, Sengupta, & Das, ). In a reverse approach, SSR signatures were also used for the identification of 208 miRNAs (including 201 novel miRNAs) in Phaseolus vulgaris (Nithin et al, ).…”
Section: Polymorphisms Involving Mirnas and Target Sitesmentioning
confidence: 99%
“…In M. truncatula, a total of 169 primer pairs were successfully designed from 130 miRNA genes (Min et al, ); (b) in lotus ( Nelumbo nucifera ), 1,000 bp sequences (500 bp flanking 5′ and 3′ ends) each in 106 pre‐miRNAs were screened for the presence of miR‐SSRs using MISA; 45 miR‐SSRs were identified in 36 genotypes (Wang, Gui, Pan, Hu, & Ding, ). (c) In tea ( Camellia sinensis ), using an online program WebSat, 18 SSRs were identified in 13 of 33 predicted miRNAs that were located in ESTs; primer pairs flanking each SSR were designed with the help of BatchPrimer3 server (Hazra, Dasgupta, Sengupta, & Das, ). In a reverse approach, SSR signatures were also used for the identification of 208 miRNAs (including 201 novel miRNAs) in Phaseolus vulgaris (Nithin et al, ).…”
Section: Polymorphisms Involving Mirnas and Target Sitesmentioning
confidence: 99%
“…The ND measures the base pair distance for all the pairs of structures (Huynen et al, 1997;Moulton et al, 2000). Previous reports have suggested that repeats of length one to six nucleotides play significant roles in functions of ncRNAs (Chen et al, 2010;Hazra et al, 2017;Jaiswal et al, 2020;Joy et al, 2013;Joy & Soniya, 2012;Mondal & Ganie, 2014;Sharma et al, 2021;Tabkhkar et al, 2020). The RNA folding measures and di-nucleotide compositions were previously employed to develop classifiers for ncRNAs (Barik & Das, 2018;Panwar et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The normalized base-pairing distance (ND) measures the base pair distance for all the pairs of structures [5,6]. Previous reports have suggested that repeats of length one to six nucleotides play significant roles in functions of ncRNAs [7][8][9][10][11][12][13]. The RNA folding measures and di-nucleotide compositions were previously employed to develop classifiers for noncoding RNAs [14,15].…”
Section: Introductionmentioning
confidence: 99%